Enlarged basal ganglia in drug-naïve patients with first-episode psychosis immediately upon symptom onset - Yeşilkaya, Ümit Haluk; Şen, Meltem; Yüzbaşıoğlu, Neslihan; Pençe, Kadriye Betül; Karamustafalioğlu, Nesrin (My University, 2024)
Objective: The basal ganglia play a crucial role in understanding the pathobiology of psychosis. While alterations in the basal ganglia are known to occur in psychosis, the timing of these alterations relative to the emergence of symptoms is not yet understood. This study aimed to investigate whether there is a change in the basal ganglia in drug-naïve first-episode psychosis (FEP) patients seeking hospital care immediately upon symptom emergence. Method: Seventy-one drug-naïve FEP patients who presented to the psychiatry outpatient clinic within the first month of symptom emergence were diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Along with 47 healthy controls (HC), they were included in the study, totaling 118 participants (64 males, 54 females). T1-weighted images were acquired through magnetic resonance imaging, and basal ganglia volume was measured using volBrain software. Symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS) by an experienced psychiatrist. Results: The volumes of the right (R) and left (L) striatum, R- and L-caudate (CAU), and R- and L- substantia nigra (SN) were found to be higher in FEP patients compared to HCs. While the volume of the L-putamen was higher, the volumes of the L-globus pallidus (GP) and L-nucleus accumbens (NAcc) were smaller in FEP compared to HCs. No significant correlation was found between volume measurements and PANSS scores. The R-CAU, L-CAU, R-Striatum, L-Striatum, L-Putamen, L-NAcc, R-GP, and L-SN were found to significantly differentiate psychosis in a univariate logistic regression model. Conclusion: From the initial stage of psychosis, even upon the immediate emergence of symptoms, the basal ganglia are affected and may play a role in the pathogenesis of the disorder.
Keywords: Basal Ganglia; First-Episode Psychosis; Magnetic Resonance Imaging; Schizophrenia